2020
DOI: 10.1002/jsfa.10880
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of physical, microstructural and antioxidative properties of pumpkin cubes cooked by conventional, vacuum cooking and sous vide methods

Abstract: BACKGROUND Current dietary guidelines recommend five or more fruit, vegetable, and legume servings per day. Often, these products are eaten cooked, resulting in organoleptic and nutritional changes. Vacuum cooking is gaining attention as an alternative cooking technique, due to its ability to preserve or even enhance sensory and healthy properties of food. Its household application is, however, poorly explored. In this work, the effect of vacuum cooking, performed with a new patented system, was studied for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…The pretreatment bananas were distinguished by lose cell-to-cell connections between them and a corresponding increase of intercellular space. The loss of cells adhesion in the cells matrix due to thermal blanching pretreatments suggests the destruction of chemical bonds between pectin polymer chains, that is, ionic bridge and Hbound (Chang et al, 1993), resulting in a middle lamellar that is depolymerized and subsequently loses its ability to bind cells (Greve et al, 1994;Rinaldi et al, 2021). Similar findings were observed in blanched carrots (Wang et al, 2021) and blanched potatoes (Roy et al, 2001).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The pretreatment bananas were distinguished by lose cell-to-cell connections between them and a corresponding increase of intercellular space. The loss of cells adhesion in the cells matrix due to thermal blanching pretreatments suggests the destruction of chemical bonds between pectin polymer chains, that is, ionic bridge and Hbound (Chang et al, 1993), resulting in a middle lamellar that is depolymerized and subsequently loses its ability to bind cells (Greve et al, 1994;Rinaldi et al, 2021). Similar findings were observed in blanched carrots (Wang et al, 2021) and blanched potatoes (Roy et al, 2001).…”
Section: Discussionmentioning
confidence: 61%
“…These cell wall characteristics are difficult to observe under a transmission electron microscope (TEM), compared with the cell wall of nonthermal blanching samples (Ahmed, Mirza, & Arreola, 1991;Roy, Taylor, & Kramer, 2001). In addition, thermal pretreatments can also cause the disintegration of the middle lamellar layer due to depolymerization of pectin chains that are contained inside it (Chang, Tsai, & Chang, 1993;Rinaldi et al, 2021). Previous studies reported that hot water or steam pretreatments decreased considerably the firmness texture and induced gelatinization of starch granules; vapor diffusion is then limited by the gelatinized layer during puffing step, which drives a larger volume expansion in the puffed starchy food (Varnalis, Brennan, & MacDougall, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Vacuum cooking is gaining popularity due to its ability to preserve or even enhance the sensory and health properties of different foods. Using pumpkin cubes as a model food, Rinaldi, et al [71] showed that vacuum cooking was more aggressive than sous vide or steaming, resulting in faster and deeper texture softening, but simultaneously less impact on pumpkin color despite the greatest extraction of some classes of carotenoids from the broken cells. In contrast, significant polyphenol extraction, especially of gallic acid and naringenin, was more efficient with sous vide and steaming pumpkins [71].…”
Section: Changes In Food Caused By Cooking and Other Processing Treat...mentioning
confidence: 99%
“…Using pumpkin cubes as a model food, Rinaldi, et al [71] showed that vacuum cooking was more aggressive than sous vide or steaming, resulting in faster and deeper texture softening, but simultaneously less impact on pumpkin color despite the greatest extraction of some classes of carotenoids from the broken cells. In contrast, significant polyphenol extraction, especially of gallic acid and naringenin, was more efficient with sous vide and steaming pumpkins [71]. On this point, it is important to note that cooking can be used to add bioactive compounds to foods.…”
Section: Changes In Food Caused By Cooking and Other Processing Treat...mentioning
confidence: 99%
“…2013; Rinaldi et al . 2021). These findings led to the development of different equipment such as the Gastrovac® (International Cooking Concepts, Barcelona, Spain) already tested in previous research (Iborra‐Bernad et al .…”
Section: Introductionmentioning
confidence: 99%